Redesign of Clove Dryer Simulation Machine Using Heat Waste of Radiator as the Heat Source - I Kadek Ervan Hadi Wiryanta (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
In this study, a redesign to a clove dryer simulation tool using exhaust heat from radiator as a source of heat energy has been done. The dryer simulation tool consists of reservoir tank, a heater, a pump to circulate the water in the system, a radiator as a heat exchanger and a drying chamber with 2 shelves. The redesign stage is carried out by fixing the piping insulation system, changing the pipe and adding valve controls to vary the velocity of the fluid flow. Variations made are variations in the mass flow rate of 0.09 kg / s and 0.18 kg /s with a constant air flow rate of 1 m/s. The results of the analysis show that at a higher mass flow rate of 0.18 kg/s the average rate of heat transfer from the radiator air side is higher, which is around 3971.65 watts. The effectiveness of the radiator will also be higher at a higher mass flow rate, the average is 0.34 at a mass flow rate of 0.09 kg/s and 0.43 at a mass flow rate of 0.18 kg /s. For drying rates with a load of 2 kg of cloves with a higher flow rate of liquid will be faster, which is about 5 hours with a flow rate of 0.18 kg/s and 6.5 hours at a flow rate of 0.09 kg/s